Inhibitory Effect of Mistletoe Ointment on DNCB-Induced Atopic Dermatitis in BALB/c Mice - Chang-Eui Hong; Su-Yun Lyu (MDPI AG, 2023)
Atopic dermatitis (AD) is increasingly prevalent globally. However, the frequent and prolonged use of corticosteroids, which are commonly employed for AD treatment, carries potential side effects. Korean mistletoe (Viscum album L. var. coloratum), a perennial parasitic plant, has demonstrated various biological effects. In this study, we conducted in vivo investigations to determine whether Korean mistletoe possesses anti-inflammatory effects that play pivotal roles in regulating the pathological mechanisms of AD. BALB/c mice with AD-like skin lesions induced by 2,4-dinitrochlorobenzene (DNCB) were utilized to explore the therapeutic effects of 1% and 2% Korean mistletoe extract (KME) ointments. The KME ointment was topically applied to the dorsal surface of the BALB/c mice, and they were categorized into four distinct groups: normal, DNCB-induced, DNCB-induced with 1% KME ointment, and DNCB-induced with 2% KME ointment. Each assessment parameter employed to evaluate the curative impact of the KME ointment displayed improvement with the application of the 1% KME ointment. While the effects observed were less pronounced than those of the 1% KME ointment, the overall therapeutic outcomes were also evident with the utilization of the 2% KME ointment. The results suggest the potential of Korean mistletoe as a viable therapeutic agent for AD. Further investigations are warranted to elucidate the underlying mechanisms of action.